Biodegradable Stents in Resistant Peptic Oesophageal Stricture: Is It the Right Way to Go?. (December 2018) - Richardson, Tom; Naidoo, Gerlin; Rupasinghe, Namal; Smart, Howard; Bhattacharya, Sayantan
Peptic oesophageal stricture can be considered as the end result of prolonged gastro-oesophageal reflux. The 'gold standard' treatment for peptic stricture is endoscopic dilatation with balloon or bougie. It is predicted that up to 40% of patients remain symptomatic with dysphagia due to refractory (resistant to treatment) or recurrent strictures, needing frequent interventions at short intervals. Such patients have poor nutritional status due to the primary disease and are susceptible to complications related to repeated endoscopic dilatation such as bleeding and perforation. This general review aims to analyse existing published evidence and address the role of biodegradable stents in resistant peptic strictures as an alternative treatment to provide long-term dysphagia-free intervals.